Compressed Collagen Enhances Stem Cell Therapy for Corneal Scarring - Shojaati, Golnar (Stem Cells Transl Med, 2018)
Stem cells from human corneal stroma (CSSC) suppress corneal stromal scarring in a mouse wound‐healing model and promote regeneration of native transparent tissue (PMID:25504883). This study investigated efficacy of compressed collagen gel (CCG) as a vehicle to deliver CSSC for corneal therapy. CSSC isolated from limbal stroma of human donor corneas were embedded in soluble rat‐tendon collagen, gelled at 37°C, and partially dehydrated to a thickness of 100 µm by passive absorption. The CCG disks were dimensionally stable, easy to handle, and could be adhered securely to de‐epithelialized mouse cornea with fibrin‐based adhesive. CSSC in CCG maintained >80% viability for >1 week in culture media and could be cryopreserved in 20% fetal bovine serum‐10%DMSO in liquid nitrogen. CCG containing as few as 500 CSSC effectively prevented visible scarring and suppressed expression of fibrotic Col3a1 mRNA. CSSC in CCG were more effective at blocking scarring on a per‐cell basis than CSSC delivered directly in a fibrin gel as previously described. Collagen‐embedded cells retained the ability to suppress corneal scarring after conventional cryopreservation. This study demonstrates use of a common biomaterial that can facilitate storage and handling of stem cells in a manner that may provide off‐the‐shelf delivery of stem cells as a therapy for corneal scarring. stem cells translational medicine 2018;7:487–494